Meet the Fockers [videorecording (DVD)] - Newman, Randy; Glienna, Greg; Clarke, Mary Ruth (Universal Studios Home Entertainment, 2005)
When Pam and Greg get their parents together it turns into one disaster after another. The hippie Fockers are the direct opposite of the uptight Byrneses. With one pitfall after the next, the film takes awkward in-law experiences to new heights.